مسیحی شعراکی نعتیہ شاعری - Bhatti, Shahzad Ahmad (Zoraiz, 2022)
This paper explores the literary and cultural significance of Urdu Naat poetry by Christian Poets who have written naat poetry inspired by their love for the Prophet Muhammad (PBUH) and desire to express their admiration for him through poetry. While mostly written by Muslim poets, some Christian poets have also written naat poetry expressing their admiration and love for the Prophet. The paper highlights the potential of this poetry to foster interfaith dialogue, and understanding, and serve as a bridge between different religious communities. It also discusses the rise of Islamophobia and anti-Muslim sentiments, and how the themes of love, devotion, and admiration for the Prophet Muhammad (PBUH) expressed in naat poetry can promote a message of tolerance and shared humanity across religious boundaries. The paper includes examples of Christian naat poets and analyzes their use of language, style, and themes to convey their message of reverence for the Prophet. One prominent example is the Pakistani Christian poet, Nazir Qaiser, appreciated for his eloquence and message of sole reverence and devotion as a humble devotee of the Prophet. Overall, the paper emphasizes the universal appeal of the teachings of the Prophet Muhammad (PBUH), regardless of one’s faith, and the potential for literature to bring people together across cultural and religious divides.